The effect of different environmental factors on force degradation of three common systems of orthodontic space closure - Morteza Oshagh; Farzaneh Khajeh; Somayeh Heidari; Sepideh Torkan; Hamid Reza Fattahi (Wolters Kluwer Medknow Publications, 2015)
Background: Different environmental conditions, such as high temperature or exposure to some chemical agents, may affect the force decay of different methods of space closure during orthodontic treatment. The aim of this in vitro study was to evaluate the force decay pattern in the presence of tea as a popular drink in some parts of the world and two mouthwashes that are usually prescribed by the orthodontist once the treatment is in progress. Materials and Methods: Elastic chain (EC), nickel-titanium (Ni-Ti) closed coil spring and tie-back (TB) method were used as the means of space closure. The specimens were placed in five different media: Hot tea, hot water (65°), chlorhexidine mouthwash, fluoride mouthwash and the control group (water at 37°). The specimens were stretched 25 mm and the elastic force of three systems was measured at the beginning of the study, after 24 h, after 1 week and after 3 weeks. One-way ANOVA was used to compare the results between the groups and Duncan test was carried out to compare the sets of means in different groups (P ≤ 0.05). Results: Tea increases the force decay in the EC and TB groups. Oral mouthwashes also resulted in more rapid force decay than the control group. EC and Ni-Ti groups were not much affected in the presence of oral mouthwashes. Conclusion: Regarding the immersion media, TB method showed the biggest variation in different media and Ni-Ti coil spring was least affected by the type of media.